Fibrogenic and fibrolytic potential of differently activated human macrophages - A. A. Maksimova; L. V. Sakhno; A. A. Ostanin (Медицинская иммунология, 2023)
Macrophages are involved in the regulation of fibrogenesis and turnover of the extracellular matrix. One way to perform this function is through the production of profibrotic and fibrolytic factors including fibronectin, laminin, collagen, and extracellular matrix proteases. The production of most of them has been well studied in experimental models; however, much remains unclear regarding human macrophages. Therefore, the aim of this study was to study the content of extracellular matrix proteases (MMP-2 and MMP-9, cathepsin L), their inhibitors (TIMP-1), and collagen (type I) in supernatants of differently activated human macrophages. We compared macrophages differentiated by M-CSF or GM-CSF and further polarized in M1 with lipopolysaccharide, in M2a with IL-4, and in M2c with dexamethasone. Macrophages was obtained from peripheral blood monocytes. The content of MMPs, TIMP, cathepsin, and collagen was determined using appropriate ELISA kits. The results obtained demonstrate that differentiation factors are more important for the production of the above factors compared to polarizing stimuli (lipopolysaccharide, IL-4, dexamethasone). Moreover, macrophages differentiated by M-CSF showed predominantly antifibrotic activity because of pronounced MMPs production, while GM-CSF-induced cultures, on the contrary, were characterized by profibrotic properties due to the high level of TIMP-1 and type I collagen. M1, M2a, and M2c, induced by M-CSF, differed only in MMP-2 production, and M2a produced this metalloproteinase more than other subtypes. In the case of GM-CSF-differentiated cells, a higher level of production of TIMP-1 and, to a lesser extent, type I collagen was characteristic of M1, whereas M2c have minimal concentration of them among GM-CSF-induced macrophage subtypes. Concerning the level of cathepsin L production was relatively constant and did not depend on the generation conditions (differentiation and polarizing signals). Thus, the data obtained help to identify macrophage subtypes with anti- or profibrotic potential and may be useful for the development of cell therapy for diseases associated with fibrogenesis dysregulation.